Profil Keterampilan Berpikir Kritis Siswa Melalui Studi Kasus di Sekolah Dasar - Hartini, Kristina Aspri; Suryandari, Kartika Chrysti; Wijayanti, Murwani Dewi; Salimi, Moh. (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Critical thinking skills are very important to be implemented since elementary education, but in practice, elementary school students still face various challenges in developing these abilities. The purpose of this study is to describe the profile of critical thinking skills of students at Paduroso Elementary School by referring to the six main indicators proposed by Facione and to identify students' strengths and weaknesses in applying critical thinking skills through a case study approach that reflects real events in the school environment, in order to provide an in-depth understanding of the actual condition of students' critical thinking abilities. Data collection activities were carried out using a qualitative approach through a case study involving 54 students from grades IV, V, and VI at Paduroso Elementary School.  Data were collected through a critical thinking test based on two real-life incidents at school: a lost shoe and a broken flower pot. Data analysis techniques used the Miles and Huberman model, which consists of data sorting, data presentation, and conclusion formulation. The results showed that the evaluation, interpretation, and self-control indicators obtained the highest scores, indicating that students' abilities to understand situations and evaluate actions reflectively were quite good. Conversely, analysis and inference were still low, indicating the need for strengthening logical thinking and drawing conclusions. This study concluded that real-life case-based and dialogic learning were effective in fostering critical thinking skills. Future recommendations include the development of systematic learning strategies that hone analytical and inferential skills, and involve the role of teachers and a supportive learning environment.Keterampilan berpikir kritis sangat penting diterapkan sejak pendidikan dasar namun pada praktiknya, siswa sekolah dasar masih menghadapi berbagai tantangan dalam mengembangkan kemampuan ini.. Penelitian ini bertujuan untuk menggambarkan profil keterampilan berpikir kritis siswa SDN Paduroso dengan mengacu pada enam indikator utama yang dikemukakan oleh Facione serta mengidentifikasi kekuatan dan kelemahan siswa dalam menerapkan keterampilan berpikir kritis melalui pendekatan studi kasus yang mencerminkan peristiwa nyata di lingkungan sekolah, guna memberikan pemahaman mendalam mengenai kondisi aktual kemampuan berpikir kritis siswa.  Kegiatan pengambilan data dilakukan dengan pendekatan kualitatif melaui  studi kasus yang melibatkan 54 siswa dari kelas IV, V, dan VI di SDN Paduroso.  Data dikumpulkan melalui tes berpikir kritis berbasis dua peristiwa nyata di sekolah, yaitu kasus sepatu hilang dan pot bunga pecah.  Tenik analisis data menggunakan model Miles dan Huberman yang terdiri dari pemilahan data, pemaparan data, dan perumusan kesimpulan.  Hasil penelitian menunjukkan bahwa indikator evalusi, interpretasi, dan pengendalian diri memperoleh skor tertinggi, menandakan kemampuan siswa dalam memahami situasi dan mengevaluasi tindakan secara reflektif cukup baik.  Sebaliknya, analisis dan Inferensi masih rendah, menandakan perlunya penguatan dalam berpikir logis dan penyusunan kesimpulan.  Penelitian ini menyimpulkan bahwa pembelajaran berbasis kasus nyata dan dialogis efektif dalam mendorong keterampilan berpikir kritis. Rekomendasi ke depan adalah pengembangan strategi pembelajaran sistematis yang mengasah kemampuan analitis dan inferensial, serta melibatkan peran guru dan lingkungan belajar yang mendukung.